Traceability matrix as a supplementary aid in system test planning - Averilla, Karen; Talisayon, Dr. Serafin (Quezon City University of the Philippines Diliman, 2010)
In today's era of high technology where the shift from traditional style workmanship to a techno savvy work environment is the trend, more and more companies are being restructured with advance technology and IT services. Automation has become the primary means of doing business be it in technical or non-technical industries. This resulted to the flourishing industry of IT and software development. With software companies abounding, one has to maximize its competitive advantage to stay in the game. Each project should be well-managed to avoid overshooting on both cost and time estimations and ending up in poor quality. Planning is very important in the software development process. An efficient plan can save up organization's time, effort and money. System Test Planning is a critical and rigorous process in software development. It involves ensuring product quality while balancing the amount of effort to be spent in product testing. As such, processes involved in this phase must be performed meticulously to generate an efficient Test Plan. This study presents a knowledge management tool that serves as a supplementary aid in system test planning for PAM, a group under the AO organization of EPM company. The tool aims to help build an efficient test estimate of documentation effort as part of the system test plan. The project also endeavors to help in identifying the documentation tasks for faster task distribution. As an end result of using the tool, this project hopes to increase product quality by making sure all aspects of the product are tested in relation to the changes in the product requirements. The development of the tool is a product of the process improvement efforts upheld by the company. It operates on the principle that at the level of daily work of the organization, quality management tools help people learn. This learning allows improvements to be made. When learning is shared among the members of the organization, knowledge and productivity increase. This is the framework that guides the project - the interaction of quality management and knowledge management at the systems level and daily work of the organization. Although the project is a result of having been identified as an area of improvement, particularly a process improvement, time constraint limits the researcher to measure the actual time improvement contributed by the use of the tool. Usability of the tool can only be measured by initial user feedback after tool completion. Actual tool usage was not gauged. Through process gap analysis, the Requirements Traceability Matrix was identified as the tool that best addresses the needs mentioned. The RTM is a type of document map that traces the relationship of requirements to the test documents. It is developed using MS Excel and housed in the company's electronic document repository. The creation, review, approval and maintenance of the tool are subject to the document control procedure of the company. At the end of the project, usability is evaluated using a survey of intended users in form of questionnaires.
All of the survey respondents agreed that this tool will make their job easier. The "ease of use" or user-friendliness averaged into a rating of 9. An average of 95 percent was obtained as the probability of using the tool on the next projects. A general positive comment was received from the respondents. By using it, test documentation tasks will be less time-consuming and the risk of missing out test documents to be updated will be lessened. Recommendations to improve the tool obtained at the end of the project were grouped into two categories based on the complexity, effort and time needed to incorporate the changes. Category 1 includes changes that are less complex and doable in a short period of time. These items are lined up for the next revision of the tool. Category 2 entails changes requiring a significant amount of effort. These items have to be reviewed internally first prior implementation. In conclusion, knowledge management tools facilitate learning and process improvements. When developing these tools, user feedback/input must be incorporated into the tool to best create its value to the users. The transfer of tacit knowledge into explicit documents is significant to achieve process improvements at the level of daily work of the organization. Improvements are best employed when they are based on employees' experience with the process or system. Hand in hand, KM and TQM in learning organizations brings about increased productivity and work quality. The paper ends with the quote that in one's work, there is always room for improvement and learning is a continuous process.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Computer software -- Development; Knowledge management -- Information technology; Traceability matrix; System Test Planning